2022
DOI: 10.3390/joitmc8020078
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Innovation in Greece: The Views of Private Health Entrepreneurs on Implementing Innovative Plans

Abstract: In the field of healthcare innovation, Greece ranks 26th in FREOPP’s World Index of Healthcare Innovation (WIHI) 2021 analysis. Such a standing illustrates low performance in the dimensions of quality, science and technology and fiscal sustainability. This article seeks to shed light on this backwardness and examine the obstacles and weaknesses in the development of innovative projects by Greek health entrepreneurs. Furthermore, this research aims to trace entrepreneurs’ views on innovation issues and assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Studies emphasize that employees will be encouraged through leadership and management (Asurakkody & Shin, 2018) and that senior management support positively affects the development of innovation practices (Aburayya et al, 2020). Another study emphasized that the legal framework and policies should support the development of innovative projects (Apostolopoulos et al, 2022). The importance of management and policy support is an undeniable fact in bringing together and sustaining all these dimensions that positively support innovation, such as innovation becoming a culture, supporting the innovation of employees, providing an environment of knowledge sharing, establishing collaboration with stakeholders, and bringing together the factors that support innovation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies emphasize that employees will be encouraged through leadership and management (Asurakkody & Shin, 2018) and that senior management support positively affects the development of innovation practices (Aburayya et al, 2020). Another study emphasized that the legal framework and policies should support the development of innovative projects (Apostolopoulos et al, 2022). The importance of management and policy support is an undeniable fact in bringing together and sustaining all these dimensions that positively support innovation, such as innovation becoming a culture, supporting the innovation of employees, providing an environment of knowledge sharing, establishing collaboration with stakeholders, and bringing together the factors that support innovation.…”
Section: Discussionmentioning
confidence: 99%
“…(Afsar & Umrani, 2020;Ahmed et al, 2019;el Desoky et al, 2021;Andiappan & Anih, 2022;Ciasullo et al, 2021;Foglia et al, 2018;Hesam Jahanmiri et al, 2021;Liu & Zeinaly, 2020;Lv et al, 2021;Marques et al, 2021;Milella et al, 2021;Mutonyi et al, 2021a;Opoku et al, 2021;Oppi et al, 2019;(Ahmed et al, 2019;Mutonyi et al, 2021a;Palm & Persson Fischier, 2021) Policy And Management Support(Aburayya et al, 2020;Asurakkody & Shin, 2018;Apostolopoulos et al, 2022;Dias et al, 2018;Marjanovic et al, 2020) Technology(Khodadad-Saryazdi, 2021;Lv et al, 2021) Our systematic analysis observed that the studies we examined were sources pointing to more than one dimension (Table1).When the studies pointing to more than one dimension are considered; human resource and leadership dimensions of the study conducted by Afsar & Umrani, 2020; leadership and knowledge acquisition and sharing dimensions of the study conducted byAsurakkody & Kim, 2020; human resource and organizational culture dimensions of the study conducted by organizational culture and technology dimensions of the study conducted by Khodadad-Saryazdi, 2021 ; human resource and knowledge acquisition and sharing dimensions of the study conducted by Liu & Zeinaly, 2020; human resource and technology dimensions of the study conducted by Lv et al, 2021; human resource and technology dimensions; Mutonyi et al, 2021a; human resource and organizational structure dimensions; Mutonyi et al, 2021b; leadership and organizational culture dimensions; Zappalà et al, 2020; human resource and leadership dimensions.…”
mentioning
confidence: 99%
“…In extreme cases, if some actors' values are not generated within the open innovation process, these actors may decide to leave the ecosystem, as in the example of the Greek ecosystem, where the health innovators abandon the ecosystem due to challenging relationships with public health structures and insurance organisations. (Apostolopoulos et al ., 2022), which may hinder their ability to generate value (Chesbrough et al ., 2018). Identifying the stakeholders is a recommended starting point for each eHealth project (Nilsen et al ., 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Finding investment for innovative solutions under strained budgets can be challenging (Gentry and Badrinath, 2017). Indeed, studies about barriers to innovation implementation in healthcare often cite reimbursement and cost issues and mention these amongst the top reasons for the non-implementation of innovation (de Grood et al ., 2016; Medlinskiene et al ., 2021; Peiffer et al ., 2019; Thijssen et al ., 2021; Warty et al ., 2021; Apostolopoulos et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This would be a new problem that does not exist in the current out-of-pocket payments. This has already been identified as a potential threat to the sustainability of private medical practices in Greece [81]. Secondly, state-owned health service providers need to be supported through targeted projects to become more competitive in the market and able to bill services to out-of-pocket patients.…”
Section: Managerial and Political Implicationsmentioning
confidence: 99%